How We Ended Racism: Realizing a New Possibility in One Generation - Williams, Justin Michael; Tygielski, Shelly (Boulder, Colorado: Sounds True, 2023)
"A look back from a future in which racism is no more-inspiring us to start taking positive action today"
Keywords: Racism -- United States; Anti-racism -- United States